Sociocultural activities at the Maternity Hospital in Oviedo: the experience of the Red Cross volunteers - Bermúdez Rey, M. Teresa (Pulso. Revista de educación, 2011)
This paper attempts to put forward the perception The Red Cross volunteers have on their sociocultural activities with pediatric inpatients endorsing at the same time the continuity of hospital animation. In 2007, a questionnaire survey was administered to 90% volunteers who carry out animation at The Maternity Hospital in Oviedo. Results show volunteers are caring young women trained by this associat ion who find their working conditions acceptable and feel their job prized by the hospital. The obtained results show the need to carry out animation in hospitals in a steady way, presumably by means of their professionalization.